Bone remodeling around stable uncemented titanium stems during the second decade after total hip arthroplasty: a DXA study at 12 and 17 years - Merle, Christian; Streit, Marcus R.; Volz, C.; Pritsch, Maria; Gotterbarm, Tobias; Aldinger, P. R. (Osteoporosis international, 2011)
Summary: In a cohort study, bone mineral density (BMD) around uncemented femoral components after total hip arthroplasty (THA) was evaluated. The results suggest that there are no clinically relevant changes in overall periprosthetic BMD in the second decade. However, continuous remodeling with limited proximal bone loss (stress-shielding) occurs, predominantly in female patients. Introduction: Progressive periprosthetic bone loss and stress-shielding are a major concern in THA. Little is known about the extent and pattern of periprosthetic bone remodeling around uncemented stems in the second decade. Methods: In a cohort study, periprosthetic BMD was measured in 131 patients with 146 uncemented CLS stems using dual-energy X-ray absorptiometry (DXA) at a mean of 12 years postoperatively (t1). Patients were followed clinically and radiographically, and a second DXA was performed at a mean of 17 years postoperatively (t2) using the identical protocol. Results: We obtained a complete set of two consecutive DXA measurements for 88 hips (78 patients, 35 male, 43 female). On radiographic evaluation at t1 and t2, regular bone ongrowth was present in all cases and no signs of radiographic loosening, severe bone loss or diaphyseal cortical hypertrophy were detected. There was no clinically relevant change in overall periprosthetic BMD (netavg) between t1 and t2 for both male and female patients. We analyzed the differences in BMD in the periprosthetic regions of interest (ROIs) according to Gruen and found a slight decrease in periprosthetic BMD in ROI 7 in male patients and in ROIs 1, 4, 6 and 7 in female patients. Conclusions: The study suggests that there are no clinically relevant changes in overall periprosthetic BMD around stable, straight uncemented stems between 12 and 17 years postoperatively. However, continuous remodeling with limited proximal bone loss occurs, predominantly in female patients. After secondary osteointegration of this implant, stress-shielding remains minimal in the second decade.
Published online: 23 November 2010
Gesehen am 18.08.2022